Using High-Pressure Technology to Develop Antioxidant-Rich Extracts from Bravo de Esmolfe Apple Residues - Mário Bordalo; Inês J. Seabra; Andreia Bento Silva; Ana Paula Terrasso; Catarina Brito; Margarida Serra; Maria R. Bronze; Catarina M. M. Duarte; Mara E. M. Braga; Hermínio C. de Sousa; Ana Teresa Serra (MDPI AG, 2021)
Bravo de Esmolfe (BE) is a traditional Portuguese apple highly appreciated by consumers due to its peculiar flavor and aroma. This apple contains higher concentration of phenolic compounds than other cultivars and is thus considered a rich source of antioxidants. Its sensorial and functional properties have attracted farmers' associations to increase BE production. However, a large quantity of apples is wasted due to storage/transportation procedures that impact BE's quality attributes. In this work, we applied high-pressure extraction methodologies to generate antioxidant-rich fractions from BE residues aiming at adding high value to these agro-food by-products. We performed a first extraction step using supercritical CO2, followed by a second extraction step where different CO2 + ethanol mixtures (10-100% v/v) were tested. All experiments were carried out at 25 MPa and 50 °C. Extracts were characterized in terms of global yield, phenolic content and antioxidant activity using chemical (ORAC, HOSC, HORAC) and cell-based assays (CAA). We demonstrated that, although the pressurized 100% ethanol condition promoted the highest recovery of phenolic compounds (509 ± 8 mg GAE/100 g BE residues), the extract obtained with 40% ethanol presented the highest CAA (1.50 ± 0.24 µmol QE/g dw) and ORAC (285 ± 16 µmol TEAC/g dw), as well as HOSC and HORAC values, which correlated with its content of epicatechin and procyanidin B2. Noteworthy, this fraction inhibited free radical production in human neurospheroids derived from NT2 cells, a robust 3D cell model for neuroprotective testing.